THE ANALYSIS OF THE VARIETAL COMPOSITION AND SOWN SEED QUALITY OF SPRING BARLEY IN THE AGRICULTURAL FARMS OF THE ROSTOV REGION - Yu. B. Arzhenovskaya; E. G. Filippov; А. А. Dontsova; G. A. Filenko (Зерновое хозяйство России, 2019)
The article presents analysis of the sown areas and spring barley productivity in the Rostov region. There has been made analysis of the cultivated varieties according to the year of their introduction into the State List of the Breeding Achievements of the Russian Federation (period-by period). There have been revealed the sown areas of spring barley varieties depending on the time spent in the production. There has been carried out the analysis of the composition of the sown spring barley seeds (original, elite and reproductive) from 2017 to 2018. There have been identified the most widely spread varieties of spring barley in the Rostov region and their reproductive composition. There has been considered expediency to improve spring barley production in the region by increasing the acreage and introducing new highly adaptable varieties.